Pengaruh Media Audio-Visual terhadap Kemampuan Mahārah Istimā' Siswa di Madrasah Tsanawiyah Negeri 3 Deli Serdang - Maylisa Putri Tambunan; Yahfidzam Yahfidzam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the effect of using audio-visual media on the mahārah istimā’ (listening skills) of grade VIII students at MTs Negeri 3 Deli Serdang. The background of this study is based on the importance of listening proficiency in Arabic language learning as a foundation for developing other language skills. This research employs a quantitative approach using a quasi-experimental design, involving two groups: an experimental group taught with audio-visual media and a control group taught conventionally. The instrument used was a listening test administered as a pre-test and post-test. The results of the t-test indicate a significant difference between the average post-test scores of the experimental and control groups. This demonstrates that audio-visual media has a positive and significant impact on improving students' Arabic listening skills. Audio-visual media effectively enhances students’ motivation, focus, and understanding of vocabulary and utterance context in Arabic.